Study of the strength of soft clay reinforced with square and triangular encapsulated bottom ash column - Nurul Aina, Husaini (2015)
Soft clay is known as problematic soil that consists of low shear strength, low permeability and high compressibility where the existing soil on the given site is unable to carry the load of proposed structure by itself, so the use of ground improvement is necessary. The stone columns are increasingly being used as ground improvement technique for supporting a wide variety of structures including buildings and flexible structures. In practice, the bearing capacity on soft clay can be improved by a layer of compacted sand or gravel. Bottom ash as by product of coal burning that has similar properties to granular material can be apply as one of the stabilizing method to the existing soil. Hence, by using bottom ash as substitute, the cost of construction can be reduced and make great progress of a growing awareness of the environmental consideration. This research discusses the results of the improvement in the shear strength of soft clay after being reinforced with a group of square and triangular encapsulated bottom ash columns. The physical and mechanical properties of the materials used such as kaolin and bottom ash were determined first. The results show that kaolin can be classified ad clayey soil and bottom ash has similarities of characteristic with granular material. A total of 52 unconfined compression tests had been conducted on kaolin specimens to determine the shear strength. The diameter for specimen is 50mm and 100mm in height. The diameter of bottom ash columns are 10mm and 16mm respectively and the height of the column are 60mm, 80mm and 100mm. The group columns have been arranged in square and triangular pattern. It can be concluded that the shear strength parameters were improved based on the different diameter and the height of the column.